Diversity of small Amazonian Dendropsophus (Anura: Hylidae): another new species from northern Bolivia - Moravec, Jiří; Aparicio, James; Guerrero-Reinhard, Marcelo; Calderon, Gonzalo; Köhler, Jörn (Zootaxa, 2008)
A new small species of Dendrospsophus is described from lowland Amazonia of the Departamento Pando, northern Bolivia. The new species is mainly characterized by smooth dorsal skin with scattered minute tubercles, relatively large distal subarticular tubercle on first toe, lack of tarsal folds, light brown to dark reddish or purple brown dorsum with numerous small dark markings and spots, dark colouration of loreal-tympanic region sharply outlined and contrasting against dorsal head colouration, one or two small white spots below the eye, yellow vocal sac in life, and advertisement call consisting of two notes with strong amplitude modulation. The new species is tentatively grouped with species placed in the Dendropsophus microcephalus group. It has rather arboreal habits and occurs in the tree canopy along swampy or flooded shores of smaller streams running through terra firme rainforest.